Morpho-Syntactic and Semantic Analysis of Aspect in English and Lithuanian - Švenčionienė, Dana (Kalbotyra, 2006)
The English and Lithuanian languages show a systematic correlation between a grammatically expressed opposition of aspects lexically and morphologically encoded in verb forms. English and Lithuanian are encoding aspectual predication syntactically and located at the interface of inflectional morphology and lexical semantics. When dealing with aspect it is important to make differences between grammatical and lexical expressions of the internal time concept of a situation. The indication of the verb tense for different situations to refer to progressive or perfect aspects in English and Lithuanian is a major problem for translators.The paper deals with the aspectual system of the verb as the predicate: translating and indicating time references of tenses their analytic and synthetic forms mostly do not match up on a one-to-one basis in such different languages as English and Lithuanian.The results of the translation analysis have a practical application in comparative syntax and typological linguistics.